Evaluación de genotipos ecuatorianos de Capsicum spp. ante infestaciones de Bemisia tabaci - Muñoz-Ponce, Steeven (2022)
The genus Capsicum, native to tropical and subtropical America, belongs to the Solanaceae family, which includes commercially important vegetables such as chilies and green peppers. The silverleaf whitefly Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae), causes losses to vegetables including Capsicum species. Among the alternatives of pest control, an effective, economical, and environmentally compatible method is the resistance of the host plant. Infestation by B. tabaci was evaluated in 73 Capsicum genotypes, corresponding to the species C. annuum, C. baccatum, C. sinense, C. frutescens and C. pubescens from an Ecuadorian genebank. Eighty-four percent of the C. baccatum genotypes evaluated showed the highest population densities of B. tabaci, while all the genotypes of C. sinense and C. frutescens had the lowest values (p < 0.05). The non-preference of adults and the scarce oviposition of B. tabaci on genotypes of C. sinense and C. frutescens suggests resistance due to antixenosis. These results could guide breeding programs for the resistance of Capsicum species to B. tabaci infestations.